The role of melatonin in red wine-induced cardioprotection - Lamont, Kim (Division of Cardiology, 2014)
Several epidemiological studies have suggested that the regular moderate consumption of red wine confers cardioprotection. However, the exact components in red wine that confer this effect are unclear. Previous studies performed in our laboratory suggest that neither the well-known polyphenol resveratrol nor alcohol (12%) present in red wine contribute to the cardioprotective effect of red wine when administered chronically, on their own. Therefore, other compounds present in red wine may contribute to its beneficial effects. The aim of the study was to explore whether melatonin, recently discovered in red wine, may play a vital role in red wine-induced cardioprotection. Furthermore, we propose that the protective effect may be mediated via the activation of the survivor-acting factor enhancement (SAFE) pathway that involves two integral components, tumour necrosis factor ± and signal transducer and activator of transcription 3 (STAT3). The drinking water of either male Wistar rats, TNF KO or STAT3 KO mice and their wild-type littermates were supplemented with a French Cabernet Sauvignon (12% alcohol by volume) or melatonin (75ng/â ) to a final concentration corresponding to the concentration found in two glasses of wine per day. After 14 days of treatment hearts were subjected to an ex vivo or an in vivo ischemia reperfusion insult or to a permanent ligation of the left descending coronary artery as a model of ischemic heart failure. Functional parameters and infarct size were assessed. The chronic moderate consumption of red wine for 14 days reduced infarct size from 60±2.3% to 23.3±1.8% after ischemia reperfusion injury, p<0.001. The pretreatment with melatonin protected to a similar extent as red wine given on its own (infarct size of 20.1±1.7%, p<0.001). Interestingly, the cardioprotective effect of red wine was partially abolished with prazosin, a melatonin receptor 3 inhibitor (40±0.9%, p<0.001 vs. wine). Furthermore, the cardioprotective effects of regular moderate consumption of red wine or melatonin were abolished in STAT3 KO and TNF KO mice. In a model of ischemic heart failure melatonin improved ejection fraction and fractional shortening compared to plain drinking water control in wild-type mice (p<0.001). The protective effect of melatonin was not abolished in TNK KO and STAT3 KO mice p<0.001 vs. control), therefore suggesting that the long-term treatment with melatonin in ischemic heart failure protects independently of the SAFE pathway. Our novel findings suggest that the moderate regular consumption of red wine (equivalent to 2-3 glasses per day) confers cardioprotection, in part due to its melatonin content. The protective effect against ischemia I/R injury of both melatonin and red wine is mediated via the activation of melatonin receptor 3 and the activation of the SAFE pathway while the protective effect of melatonin against ischemic heart failure is independent of the SAFE pathway. Melatonin is a safe, cheap and easily accessible drug that may be considered as an innovative therapeutic agent in the treatment against acute myocardial infarction and ischemic heart failure.